Analysis of spatial distribution of noiseon Adam Mickiewicz housing estate in Lublin - Joachimowicz, Aleksandra; Nieścioruk, Kamil (Budownictwo i Architektura / Civil and Architectural Engineering, 2019)
The paper deals with the problem of measuring and analysing noise in resi-dential areas with relation to their vicinity and landscape- and architecture composition. Al-most 70 points were selected to measure the noise three times per day and to create, using GIS tools, spatial image of the phenomenon. The resulting maps were analysed, pointing out sources of noise and factors reducing the sound spread. The further research ideas were suggested as well.